Chronic eczematous dermatitis in patients with neurodegenerative diseases may be an early marker of bullous pemphigoid. (June 2017) - Chou, Ping-Song; Chou, Tsai-Ching; Chang, Chung-Hsing; Yu, Sebastian; Lee, Chih-Hung
Abstract: The number of elderly patients with chronic pruritus has been gradually increasing in aging countries. Bullous pemphigoid, a common autoimmune blister disease in the elderly, is always heralded by pruritic eczematous dermatitis and is often associated with neurodegenerative diseases. We hypothesized that chronic eczematous dermatitis in patients with neurodegenerative diseases may be an early marker of bullous pemphigoid. By conducting retrospective chart review, we found neurodegenerative diseases are more prevalent in elderly patients with chronic eczematous dermatitis. The mean time delay between the diagnosis of neurodegenerative diseases and onset of skin lesions is 4.17 years. In all 6 patients who received skin biopsy, eosinophils in the upper dermis or at the dermo-epidermal junction were obvious, which are remnant of the pathological finding of bullous pemphigoid. Together with the well-known association between bullous pemphigoid and neurodegenerative diseases, the results suggested that unlocalized eczematous dermatitis in the elderly may be an early manifestation of bullous pemphigoid. Inter-discipline communication among neurology, dermatology and geriatrics/gerontology is required to tailor specific managements for elderly patients with pruritus and neurodegenerative diseases.